Substitution of Cassava Peel Flour In Making Siomai Skin - Anggita Dwirevyanti; Atat Siti Nurani; Ai Mahmudatussa'adah (Universitas Pendidikan Indonesia (UPI), 2021)
Cassava peel flour comes from the cassava plant which has several ingredients that are beneficial to the body, including 8.11 grams of protein, 15.20 grams of crude fiber, 0.22 grams of pectin, 1.29 grams of fat, 0.63 grams of calcium. Utilization of cassava peel flour can be developed into a food preparation as a substitute for some of the use of wheat flour, one of which is making siomay skin by using cassava peel flour substitution. The purpose of this study was to determine consumer acceptance of siomay skin products with cassava peel substitution based on color, aroma, texture, taste, and overall impression. This study used experimental methods and RAL design (completely randomized design). The development of siomay skin products with cassava peel flour substitution was carried out by replacing some of the use of wheat flour by substituting cassava peel flour in making siomay skins with 3 treatments, 245 (20% cassava peel flour: 80% wheat flour), 425 (cassava peel flour) 30%: 70% wheat flour), 542 (cassava peel flour 50%: 50% wheat flour). The instrument used to measure consumer acceptance was using a questionnaire with a Likert scale in the form of a checklist and using a semi-trained panel of 20 people. Acceptance analysis is done by analyzing the data that has been collected which is then processed using descriptive analysis with interval class sizes. The results showed that the product with the code 245 was the product with the highest level of acceptance by consumers. Based on the overall results, product 245 is the recommended product for production.